Behavioural Insights: Where the Rubber Needs to Meet the Ottawa Road - Kohos, Erica (Université d'Ottawa | University of Ottawa, 2014)
The decade long-search for more efficient policy making strategies and service delivery programs has left governments around the world sympathetic to human vulnerability, and advantaged by the insight to manipulate environments and effectively shape choices. This research paper explores the offerings of behavioural economics (BE) in so far as behavioural insights (BI) can contribute to shaping more effective and more desirable long-term outcomes of policy making and program delivery. Foundational to this study are three questions. What potential do behavioural insights have for advancing the Government of Canada’s (GC) priorities, especially as they pertain to the public service and the creation of policy? What are the potential areas of concern if the GC is to incorporate behavioural insights into its policy making toolkit? How ought the GC to adopt behavioural insights as a tool of policy making so as to ensure compliance with a policy model of governance? First a review of the failings of the conventional neoclassical economic models makes evident the need and context for the collaborative multidisciplinary field of BE. Following which a review of behavioural insights and “nudging” in public policy and public service delivery internationally, using Caroline Oliver’s (2002) model of policy governance,identifies some of the trends apparent in current practical examples of nudging. To explore the Canadian context before making recommendations, a case study approach is used to analyze three current Canadian applications of BI. Case studies are most useful because as a tool BI is still in its infancy in Canada and the local data available is quite limited and mostly anecdotal in the form of government reporting. Based on the discussion of current examples and areas of concern, three recommendations are made to government: 1. GCanada ought to establish a change lab or innovation hub as a permanent residence for the BI mandate, including the responsibilities to staff the task team in accordance with the model of governance to ensure that the governing body has the capacity and competence to fulfil its mandate (Oliver, 2002). As such all staffing processes should include both internal and external competitions. 2. Appropriate stakeholders should be identified and clear working relationships should be established with them, so that they can be involved in the assembly of an oversights team to ensure that the requirements for accountability are fulfilled. 3. Mechanisms for accountability and reporting must be established to ensure that the productive impact to all Canadians is verifiable and available to all Canadians in open format per current Government priorities.